The spa - Weldon, Fay (Grove Press, 2007)
A group of ten high-powered, accomplished ladies gathers at the expensive Castle Spa, seeking to rejuvenate themselves--through Botox, aromatherapy, and general pampering--and telling one another the stories of their lives.